2020
DOI: 10.3390/ph13090209
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Rofecoxib-Based Cyclooxygenase-2 Inhibitors: A Bioinformatics Approach

Abstract: The cyclooxygenase-2 receptor is a therapeutic target for planning potential drugs with anti-inflammatory activity. The selective cyclooxygenase-2 (COX-2) inhibitor rofecoxib was selected as a pivot molecule to perform virtual ligand-based screening from six commercial databases. We performed the search for similarly shaped Rapid Overlay of Chemical Structures (ROCS) and electrostatic (EON) compounds. After, we used pharmacokinetic and toxicological parameters to determine the best potential compounds, obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 110 publications
0
24
0
2
Order By: Relevance
“…After the application of the reduction and selection filters of the 2000 compounds, they were submitted to similarity to Tanimoto to find out which ones are closer to the characteristics of the pivot molecule used in the process (Rofecoxib). The fifty eight (58) molecules were obtained with a Tanimoto index greater than 0.35 (see Table 6), which is a value that is considered reasonable for the application of toxicological and pharmacological prediction studies in silico, with three promising molecules being selected during these tests as reported below, subsequently applying the molecular coupling and molecular dynamics tests [18]. Table 7 shows the best results of the toxicological tests applied to the three inhibitors selected through the Tanimoto index and tests performed through the online server PreADMET (https: //preadmet.bmdrc.kr/adme/) in order to screen those who present better absorption, distribution, and metabolism values besides limiting the possibilities of mutagenicity through toxicological tests.…”
Section: Pharmacophore Characteristicsmentioning
confidence: 99%
“…After the application of the reduction and selection filters of the 2000 compounds, they were submitted to similarity to Tanimoto to find out which ones are closer to the characteristics of the pivot molecule used in the process (Rofecoxib). The fifty eight (58) molecules were obtained with a Tanimoto index greater than 0.35 (see Table 6), which is a value that is considered reasonable for the application of toxicological and pharmacological prediction studies in silico, with three promising molecules being selected during these tests as reported below, subsequently applying the molecular coupling and molecular dynamics tests [18]. Table 7 shows the best results of the toxicological tests applied to the three inhibitors selected through the Tanimoto index and tests performed through the online server PreADMET (https: //preadmet.bmdrc.kr/adme/) in order to screen those who present better absorption, distribution, and metabolism values besides limiting the possibilities of mutagenicity through toxicological tests.…”
Section: Pharmacophore Characteristicsmentioning
confidence: 99%
“…In the past numerous molecules of non-antibiotic nature earlier acknowledged as anthelmintics, anticancer drugs, antipsychotics, antidepressant drugs, antiplatelets and NSAIDs have been evaluated for their antimicrobial potential (3, 4). Some of the cyclooxygenase inhibitory anti-inflammatory and antipyretic drugs (5) such as acetaminophen (paracetamol), acetylsalicylic acid (aspirin), diclofenac and ibuprofen, flurbiprofen and similar non-steroidal anti-inflammatory drugs (NSAIDs) almost consistently used along with antimicrobial therapy have also been explored for their antimicrobial potential. The most commonly used on-counter NSAIDs (aspirin and paracetamol) are known less for their antibacterial activity in acceptable therapeutic dosages but are reported to enhance the performance of antibiotics either through their synergistic antibacterial action with antibiotics (6–9) or through reducing adherence, production of biofilm, and other virulence factors, and altering antibiotic susceptibility of pathogens (4, 5).…”
Section: Introductionmentioning
confidence: 99%
“…In silico molecular docking simulations have been applied to investigate the interaction of bioactive compounds of natural origin with proteins of pharmacological interest [36,37] . We used this technique to investigate whether benzaldehyde, a major compound in essential oil from Bignonia nocturna , is capable of interacting with the acetylcholinesterase (AChE) protein.…”
Section: Resultsmentioning
confidence: 99%